Enhancing Elementary Mathematics Learning Through Contextual Teaching and Regalia: A Case Study in Blora, Indonesia - Muhammad Budiman; Nurun Nimah; Murot Bozorov (Jurnal Pendidikan Guru Sekolah Dasar, 2025)
This study explores the implementation and perceived effectiveness of contextual teaching supported by regalia in elementary mathematics classes. A qualitative case study approach was adopted, employing in-depth interviews with a fifth-grade mathematics teacher in Blora, Indonesia, as the primary data source. The findings reveal that the integration of contextual teaching with regalia strengthens students’ conceptual understanding, engagement, motivation, and creativity during mathematics learning activities. Regalia enabled students to actively manipulate instructional objects, helping them connect mathematical ideas with real-world contexts. However, the approach presented challenges, including limited availability of instructional media and substantial preparation time required for classroom use. Despite these constraints, the study concludes that contextual teaching using regalia is an effective strategy for improving mathematics learning in elementary schools. The results also provide practical guidance for educators seeking meaningful, hands-on instructional approaches that encourage student participation and deeper understanding.